Nonconvulsive Seizures and Brain Damage - J Gordon Millichap (Pediatric Neurology Briefs)
Possible brain damage resulting from nonconvulsive seizures is debated “for” by Young GB and Jordan KG (Department of Clinical Neurological Sciences, 375 South St, London, Ontario, Canada N6A 4G5), and “against” by Aminoff MJ (Box 0114, Room M-794, Department of Neurology, School of Medicine, University of California, San Francisco, CA 94143).